Two Studies Investigating Gender Differences in Response to Facebook Status Updates - Joiner, Richard; Dapkeviciute, Lina; Johnson, Helen; Gavin, Jeff; Brosnan, Mark (Proceedings of the International AAAI Conference on Web and Social Media, 2021)
We conducted two studies to examine gender differences in in response to Facebook status updates. The first study surveyed 600 undergraduate students (388 females and 207 males), and analysed males’ and females’ responses to Facebook status updates. Females were significantly more likely to post a public reply than males, and female public replies also contained higher levels of emotional support. There were no significant gender differences in private replies to Facebook status updates. Males showed significantly higher levels of emotional support in private messages than in public replies. There was no significant difference in terms of level of emotional support between females’ public replies and private messages. The second study investigated gender differences in response to Facebook status updates from same gender friends compared to opposite gender friends. We surveyed 522 undergraduate students (216 females and 306 males), and analysed males’ and females’ responses to two Facebook status updates: one from a same gender close friend and one from an opposite gender close friend. Females showed higher levels of emotional support than males to a Facebook status update from a same gender friend. In contrast, there were no significant gender differences in response to an opposite gender friend. Males showed higher levels of emotional support in private replies than public replies to same gender friends. There was no difference in level of emotional support between females’ public replies and private messages. The implications of these findings for explanations of gender differences in language use are discussed